The Neutral Theory of Evolution - Chambers, Geoffrey (New Zealand Science Review, 2020)
Today most people are perfectly happy to accept Charles Darwin’s ideas about ‘evolution by means of natural selection’ as the dominant paradigm in biology. So many of us may be quite surprised to know that this has not always been the case among professional biologists. First, the very idea of evolution as ‘descent with modification from ancestral forms’ predates Darwin (see below). Second, during his own lifetime Darwin’s account was overshadowed in the imagination of the Victorian public by Robert Chambers’ 1844 speculative work Vestiges of the Natural History of Creation.This book invokes quite differ-ent processes driving evolution – sometimes called a mixture of magick plus the ‘inheritance of acquired characteristics’ (and following Jean-Baptiste Lamarck in this latter idea). However, it was Darwin’s version that the scientists of the day preferred. His greatest achievement became recognised as his hypothesis of ‘natural selection’ being the most rational explanation of the process driving evolution. This makes the notion of evolution per se logically acceptable as accounting for the history of life on our planet. So, it is almost unthinkable that during the succeeding century Darwin’s ideas would face serious challenges and even outright rejection from biologists. Even more so that this hap-pened twice! Indeed, today it is well and widely understood that evolution will still proceed even in the absence of natural selection. Biologists and philosophers now recognise that a key vulnerability in Darwin’s writing was his very sketchy knowledge of genetics. Specifically, it is our later knowledge of mutational processes and the distribution of naturally occurring genetic variants that led to conflict with Darwinian thinking. This article is concerned with the second of these periods of controversy arising from Motoo Kimura’s so-called Neutral Theory. The author of this present article devoted a large part of his early career to participation in laboratory investigations around this question and these experiences form the basis for this account. But, before one can begin to explore this topic, it is necessary to examine its origins.